If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8u + -10 + 6u + -8 = 78u + -24 Reorder the terms: -10 + -8 + 8u + 6u = 78u + -24 Combine like terms: -10 + -8 = -18 -18 + 8u + 6u = 78u + -24 Combine like terms: 8u + 6u = 14u -18 + 14u = 78u + -24 Reorder the terms: -18 + 14u = -24 + 78u Solving -18 + 14u = -24 + 78u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-78u' to each side of the equation. -18 + 14u + -78u = -24 + 78u + -78u Combine like terms: 14u + -78u = -64u -18 + -64u = -24 + 78u + -78u Combine like terms: 78u + -78u = 0 -18 + -64u = -24 + 0 -18 + -64u = -24 Add '18' to each side of the equation. -18 + 18 + -64u = -24 + 18 Combine like terms: -18 + 18 = 0 0 + -64u = -24 + 18 -64u = -24 + 18 Combine like terms: -24 + 18 = -6 -64u = -6 Divide each side by '-64'. u = 0.09375 Simplifying u = 0.09375
| (7x+11)-(9x-7)= | | 56x^2-126x+35=0 | | (8x+3)-(3x+8)= | | 6x^3+24x=0 | | x^2-30x-31=0 | | 16e+6=7e-21 | | ln(x)+ln(5x)=-3 | | 3(9-4)-6(4-9)= | | (2x^2+4x-8)+(-2x+3)= | | 3x+5y-(2x-3y)= | | x^2+2*x+2=0 | | 15x^2-86x-24=0 | | x^2+11x-9c+12=0 | | (3x-7)+(-4x-2)= | | x^3+x^2+7x+21= | | 6b^2+b-57=0 | | 5n-11=3n-19 | | -5(k+7)+5k= | | 12X^2+32X+21=0 | | 4-2(v-6)=-6 | | 4x^2+30=46 | | -7x+6z-y-x+12y+4z-6z+2y-11x= | | 15t^2+45t+10=40 | | -1/6(x-12)+1/2(x+2)=x+15 | | 1000+30m=e | | x^2+25x+11= | | -(5y+3)-(-4y-4)=-5 | | 20b-20b= | | (X-10)(X-10)+(X+10)(X+10)= | | .75x-1=12 | | (2x+8)(2x-8)= | | x^2+-11x+30= |